A success story: water primroses, aquatic plant pests. Issue 5 (13th August 2013) - Thouvenot, Lise; Haury, Jacques; Thiebaut, Gabrielle
ABSTRACT Aquatic ecosystems are currently invaded by non‐indigenous aquatic plants. A major challenge for biological invasion research is to develop the ability to predict the spread of species. Throughout the world, Ludwigia peploides subsp. montevidensis and Ludwigia grandiflora subsp. hexapetala are now considered to be two of the most invasive aquatic plants. This paper reviews the scientific knowledge about these species, their ecological and socio‐economic impacts and methods of management. Water primrose possesses some advantageous biological traits, such as rapid growth rate, efficient reproductive capacity, high plasticity in growth response, broad ecological tolerance and allelopathic compounds which might explain its expansion and colonization of numerous ecosystems. Much attention must be paid to Ludwigia grandiflora subsp. hexapetala and Ludwigia peploides subsp. montevidensis. According to climatic models, global warming will further increase the spread of these species in Europe. Copyright © 2013 John Wiley & Sons, Ltd.